EVALUASI SISTEM AKUNTANSI PEMBELIAN TUNAI PADA TOKO ROXY SWALAYAN ENDE - Ado, Basilius Padi; Marselina, Apriana; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2024)
The cash sales accounting system is a unified unit of cash sales system elements and works together which includes functions related to documents and records used as well as internal controls governing cash sales activities. The cash sales accounting system implemented by the company will not run well if it is not balanced with a good internal control system. The purpose of this study was to determine the cash sales accounting system at Roxy Supermarkets Ende. The method used is descriptive qualitative method. Data collection techniques used are observation, interviews, documentation and literature study. The results showed that (1) Functions related to sales transactions were sales function, cash function, warehouse function, shipping function and accounting function. (2) The documents used by Roxy Supermarkets consist of cash sales invoices and proof of bank deposits in accordance with the theory put forward by Mulyadi. However, there are several documents such as cash register tapes, bills of lading, COD sales invoices, recapitulation of cost of goods sold, and proof of memorials that are not applied to Roxy Supermarkets. (3) Accounting records, namely sales journals, cash receipts journals, inventory card general journals, and warehouse cards, have not been applied to Roxy Supermarkets. (4) The cash sales accounting system procedure network used by Roxy Supermarkets consists of sales order procedures, cash receipt procedures, goods delivery procedures, and cash deposit procedures which are in accordance with Mulyadi's theory. However, there are several procedures for the cash sales system that are not implemented at Roxy Supermarkets, namely the procedure for recording cash sales, the procedure for recording cash receipts, and the procedure for recording the cost of goods sold.